Visible Light Communication System Design Using Raspberry Pi4B, LED Array, and MQTT Synchronization Protocol - Teuku Alif Rafi Akbar; Apriono Catur (Universitas Ahmad Dahlan, 2023)
Visible light communication emerged as the solution to overcome limitations exist in RF-based communication system. Although many research has been done on VLC, there are still a lot room for improvements, especially in the design of the VLC itself. This study discusses a simple visible light communication system design that transmits temperature and humidity information. The system uses Array 2×2 LED configuration to transmit data and photodiode to receive the optical signal. Raspberry Pi is used as the signal processor. The research carried out variations in the color of LED used, variations in the method of synchronization, and variations in the data rate transmission with BER value as the main parameter to be analyzed. The research contribution is to propose a simple visible light communication design that transmit and receive information in reference to room temperature and humidity using Raspberry Pi and DHT-11 sensor, while also implementing two synchronization methods to maximize synchronization in transmission thus minimizing the BER value in higher bit rate. The LED used is blue with an average voltage of 0.0423 V for bit ‘1’ and 0.00448 V for bit ‘0’. The throughput can be achieved are within range 1bps to 10 kbps with BER 0.5 as a threshold. The implementation of the synchronization method decreases the average BER value by 0.0945 with the implementation of transmission calibration synchronization and decreases the average BER value by 0.1221 using the MQTT communication protocol. In conclusion, the design has limitations through the component used in the transmitting and receiving end with BER values relatively high. Further research for system development can be done by implementing Forward Error Correction to minimize errors that occur in the transmission and collaborating with vendors with same research field for the latest components for VLC system design.